Mineralization Potential of Electrospun PDO-Hydroxyapatite-Fibrinogen Blended Scaffolds - Isaac A. Rodriguez; Parthasarathy A. Madurantakam; Jennifer M. McCool; Scott A. Sell; Hu Yang; Peter C. Moon; Gary L. Bowlin (International Journal of Biomaterials, 2012)
The current bone autograft procedure for cleft palate repair presents several disadvantages such as limited availability, additional invasive surgery, and donor site morbidity. The present preliminary study evaluates the mineralization potential of electrospun polydioxanone:nano-hydroxyapatite : fibrinogen (PDO : nHA : Fg) blended scaffolds in different simulated body fluids (SBF). Scaffolds were fabricated by blending PDO : nHA : Fg in the following percent by weight ratios: 100 : 0 : 0, 50 : 25 : 25, 50 : 50 : 0, 50 : 0 : 50, 0 : 0 : 100, and 0 : 50 : 50. Samples were immersed in (conventional (c), revised (r), ionic (i), and modified (m)) SBF for 5 and 14 days to induce mineralization. Scaffolds were characterized before and after mineralization via scanning electron microscopy, Alizarin Red-based assay, and modified burnout test. The addition of Fg resulted in scaffolds with smaller fiber diameters. Fg containing scaffolds also induced sheet-like mineralization while individual fiber mineralization was noticed in its absence. Mineralized electrospun Fg scaffolds without PDO were not mechanically stable after 5 days in SBF, but had superior mineralization capabilities which produced a thick bone-like mineral (BLM) layer throughout the scaffolds. 50 : 50 : 0 scaffolds incubated in either r-SBF for 5 days or c-SBF for 14 days produced scaffolds with high mineral content and individual-mineralized fibers. These mineralized scaffolds were still porous and will be further optimized as an effective bone substitute in future studies.